Relationship Between Blood Mercury Concentration and Waist-to-Hip Ratio in Elderly Korean Individuals Living in Coastal Areas - You, Chang-Hun (The Korean Society for Preventive Medicine, 2011)
OBJECTIVES: This study investigated the relationship between the blood mercury concentration and cardiovascular risk factors in elderly Korean individuals living in coastal areas. METHODS: The sample consisted of 477 adults (164 males, 313 females) aged 40 to 65 years who visited a Busan health promotion center from June to September in 2009. The relationship between blood mercury concentration and cardiovascular risk factors including metabolic syndrome, cholesterol profiles, blood pressure, body mass index (BMI), waist circumference and waist-to-hip ratio (WHR), was investigated. Variables related to blood mercury concentration were further evaluated using multiple regression analysis. RESULTS: The blood mercury concentration of the study population was 7.99 (range, 7.60 to 8.40) µg/L. In males, the blood mercury concentration was 9.74 (8.92 to 10.63) µg/L, which was significantly higher than that in females (7.21, [6.80 to 7.64] µg/L). The blood mercury concentration of the study population was related to several cardiovascular risk factors including low-density lipoprotein (LDL) cholesterol (p=0.044), high-density lipoprotein (HDL) cholesterol (p=0.034), BMI (p = 0.006), waist circumference (p = 0.031), and WHR (p < 0.001). In males, the blood mercury concentration was significantly correlated with WHR in the multiple regression analysis. CONCLUSIONS: In males, the blood mercury concentration was related to waist-to-hip ratio, which is a central obesity index and cardiovascular risk factor. Our finding suggests that cardiovascular disease risk in males was increased by mercury exposure via an obesity-related mechanism.